Determination of attitudes and opinions of triathlon athletes regarding doping as a moral issue - Celebi, Evrim; Gundogdu, Cemal; Tufekci, Sakir (Kamala-Raj Enterprises, 2018)
This study aims to determine the attitudes and opinions of triathlon athletes on the use of doping in sports as a moral issue. This descriptive study was conducted on 92 athletes. The data were collected using a questionnaire. Regarding the attitudes and opinions of athletes included in the research regarding the use of doping were looked through, the athletes were found to “agree” with the statements of “Use of doping in sports gives an unfair advantage” (98.9%), “Doping is a very serious problem in the world of sports” (97.8%), “Doping causes severe damage to health” (93.5%), “The use of doping is contrary to the ethics of sport” (91.3%), nevertheless the athletes were found to “disagree” with the following statements: “The use of doping in sports should be allowed” (90.2%), “I’ll use doping for the success of my country in an international organization” (92.4%), “I’ll use doping as long as it goes unnoticed” (91.3%). As a result, the majority of athletes thinks that doping leads to unfair competition in sports, damages health and it’s a serious problem for the sports world, as well as being contradictory with the ethics of sport. © Kamla-Raj 2018.
Keywords: Doping; Doping attitude; Ethics; Triathlete